Dunia Islam: Posisi dan Problematika Umat Islam di Asia Selatan, Mazhab dan Solusinya - Rasyid, Soraya (Jurnal Adabiyah, 2010)
There are many references relating Islamic world in South Asia. It muchly focus on dinasty and its corelation with ecomic, social, religious and cultural aspects. The hypothesis is that historically, the early Islamic existence is began with attack, conquest and building Islamic Kingdom. South Asia covers; India, Pakistan, Sri Langka, Maladewa, Kashmir, with its demography comprised 300 million population with different languages and cultures. In the post colonialism, Islam has degraded due to political crises and the emerge of sufism sincritism.